Isolation and characterization of microsatellites in Echinochloa (L.) Beauv. spp. - Danquah, E.Y.; Hanley, S.J.; Brookes, R.C.; Aldam, C.; Karp, A. (Molecular Ecology Notes, 2002)
Five primer pairs were developed that amplify microsatellite loci in three agronomically important Echinochloa (L.) Beauv. species: E. colona (L.) Link, E. crus-galli (L.) Beauv. and E. crus-pavonis (Kunth) Schultes. The microsatellites were tested on 24 individuals representing three species collected in rice fields from different geographical regions and revealed 3-7 alleles per microsatellite. Gene diversity [1 - σpij 2] for four polymorphic loci within E. crus-galli ranged from 0.12 to 0.61. Alleles at a fifth locus were useful in discriminating the species. The microsatellites should provide useful markers for intraspecific diversity studies and aid classification of species within this complex genus.
Keywords: Echinochloa; Microsatellites; Polymorphism; Weeds